Farmers’ adoption and willingness to pay for certified aromatic rice seed in the Mekong River Delta, Vietnam - Thi Pham, Nguyen; Napasintuwong, Orachos (Institute of Agricultural Management, 2020)
As preferences and patterns of demand are shifting towards higher quality rice, Vietnam is exploring options to expand aromatic rice production. In recent years, there has been an intensified effort to promote high-quality seed adoption to produce better quality rice and therefore raise the value of exported rice. Financial indices, logit models were used to illustrate farmers’ attitudes and expectations towards certified aromatic rice seed, to identify the factors influencing their adoption decision and willingness-to-pay. These issues were examined by drawing on a sample of 306 farmers in winter–spring 2016/2017 in the Mekong River Delta, Vietnam. Private company and farmer-saved seed were the main aromatic rice seed suppliers for the adopter group and the non-adopter group, respectively. Agricultural organisation membership, perceived profitability advantages, lower seed rate and greater availability of certified aromatic rice seed were the key incentives to the adoption of certified aromatic rice seed. Willingness-topay for certified aromatic rice seed was 11,986 VND/kg, which was lower than the current market price. Consequently, encouraging suppliers to guarantee certified aromatic rice seed availability at an affordable price and identifying solutions to increase the price of rice should be supported by government policy